2008
DOI: 10.1055/s-0028-1090598
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Prolonged Bedside Amplitude-Integrated Encephalogram in Encephalopathic Infants

Abstract: We hypothesized that prolonged bedside limited-channel amplitude-integrated electroencephalogram (aEEG) monitoring following a standard 1-hour conventional electroencephalogram (cEEG) would increase the detection of subclinical seizures and allow continuous evaluation of the background EEG in neonatal encephalopathy. This may identify complementary roles for these EEG technologies in neonatal units where continuous cEEG monitoring may not be readily available. We prospectively recruited 25 term neonates with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
0
10
0
2
Order By: Relevance
“…Our results suggest that aEEG might be overall easier to interpret which could explain why combining aEEG with CDSA appeared to improve seizure detection rates over CDSA alone. aEEG displays seizures as changes in peak-to-peak amplitude (19, 24) whereas CDSA displays seizures as high power through a Fourier transformation of both amplitude and frequency(15). CDSA provides a different dimension to seizures with color displays of power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that aEEG might be overall easier to interpret which could explain why combining aEEG with CDSA appeared to improve seizure detection rates over CDSA alone. aEEG displays seizures as changes in peak-to-peak amplitude (19, 24) whereas CDSA displays seizures as high power through a Fourier transformation of both amplitude and frequency(15). CDSA provides a different dimension to seizures with color displays of power.…”
Section: Discussionmentioning
confidence: 99%
“…CDSA uses Fourier transformation to present EEG power (amplitude 2 /Hz) (color) and frequency (y-axis) over time (x-axis). They both have the advantage of displaying several hours of compressed EEG data as a single image (15, 19, 24)(Figure 1). …”
Section: Introductionmentioning
confidence: 99%
“…Several studies examined the utility of aEEG in comparison with conventional and/or video-EEG in this infant population, finding that aEEG was not only reliable but also complemented cEEG in more than one aspect. 14,26 A recent pilot study on the feasibility of aEEG in our tertiary-care NICU showed that 73% of seizures >30 s and 87% >60 s were detected by the aEEG seizure algorithm. 27 Furthermore, when compared with a blinded study group, patients whose tracings were visible to bedside physicians showed a trend toward reduced seizure burden without evidence of overtreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Rutin yenidoğan cEEG'sinin akut, ağır beyin hasarı sonrasında kalıcı nörolojik sekel ve ölüm açısından prognostik değeri birçok çalışma ile kanıtlanmıştır (14,15). İdeal olan, şüpheli nöbetleri olan yenidoğanlarda video monitörizasyonu ile birlikte uzun cEEG çekimidir (7). Ancak standart klinik uygulamalarda genellikle cEEG çekimi 30-60 dakika ile sınırlıdır.…”
Section: Gereç Ve Yöntemunclassified
“…Bununla birlikte elektrografik yenidoğan nöbetlerinin çoğu subkliniktir. Serebral aktivitenin sürekli monitörizasyonu; serebral hasarın derecesi ve prognozun değerlendirilmesine, nöbet aktivitesi ve tedaviye yanıtın monitörize edilmesine katkıda bulunabilir (4)(5)(6)(7). Ayrıca nöroprotektif tedavi için uygun olan yenidoğanların erken dönemde belirlenmesine yardımcı olur (8,9).…”
Section: Introductionunclassified